The Challenges Of Malaysia Educational Leaders During The Covid-19 Movement Control Order (MCO) - Ahmad Zaharuddin Sani; Roziya Abu; Badruddin Kaddas (Lembaga Sembilan Tiga Community, 2021)
Trials and challenges of world education come alternately. In general, when something unexpected happens, leaders need to be proficient in it adapting to sudden changes, improving the decision, creativity, decision making through collaborative action (collaboration), and trustworthiness. Every leader in an organization needs to know and take risk management strategies to continue to be implemented in new work culture. The covid-19 pandemic crisis is a risk that leaders need to face. Therefore, in addressing this world of the pandemic, new challenges for leaders need to be flexible and various. This paper is a suggestion or policy paper to be adhered to by a new leader or academician in facing this tragic situation. In summary, the level of readiness and sensitivity of educational leaders to change the ever-changing world environment needs to be always high and dynamic in shouldering the responsibility of performing daily tasks. Trials and challenges of world education come alternately.